Memorandum of Understanding (Micro-Capital grant agreement) between the United Nations Development Programme (UNDP) and Institute of Governance Studies, BRAC University (2011) - United Nations Development Programme (UNDP); Institute of Governance Studies, BRAC University (United Nations Development Programme (UNDP) and Institute of Governance Studies, BRAC University, 2013)
This Memorandum of Understanding is provided as a tool that can be adapted to the specific needs of a particular programme. Micro-Capital Grant Agreements should be approved by an independent mechanism such as a steering committee or Steering Committee. This grant agreement serves to register the commitments and results that the recipient institution has agreed to produce. It is recommended that funds be released in tranches, based on results. These results should be clearly specified, such that it is clear to all parties when a recipient institution qualifies for release of tranches of funds.